The Versatile Roles of Sulfur-Containing Biomolecules in Plant Defense—A Road to Disease Resistance - András Künstler; Gábor Gullner; Attila L. Ádám; Judit Kolozsváriné Nagy; Lóránt Király (Plants, 2020)
Sulfur (S) is an essential plant macronutrient and the pivotal role of sulfur compounds in plant disease resistance has become obvious in recent decades. This review attempts to recapitulate results on the various functions of sulfur-containing defense compounds (SDCs) in plant defense responses to pathogens. These compounds include sulfur containing amino acids such as cysteine and methionine, the tripeptide glutathione, thionins and defensins, glucosinolates and phytoalexins and, last but not least, reactive sulfur species and hydrogen sulfide. SDCs play versatile roles both in pathogen perception and initiating signal transduction pathways that are interconnected with various defense processes regulated by plant hormones (salicylic acid, jasmonic acid and ethylene) and reactive oxygen species (ROS). Importantly, ROS-mediated reversible oxidation of cysteine residues on plant proteins have profound effects on protein functions like signal transduction of plant defense responses during pathogen infections. Indeed, the multifaceted plant defense responses initiated by SDCs should provide novel tools for plant breeding to endow crops with efficient defense responses to invading pathogens.